2002
DOI: 10.1046/j.1365-3016.2002.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal second‐trimester serum ferritin concentrations and subsequent risk of preterm delivery

Abstract: We studied the relationship between maternal second-trimester serum ferritin concentrations and preterm delivery. The 312 preterm delivery cases, studied in aggregate and in subgroups [spontaneous preterm labour, preterm premature rupture of membranes, medically induced preterm delivery, moderate preterm delivery (gestational age at delivery 34-36 weeks) and very preterm delivery (gestational age at delivery <34 weeks)] were compared with 424 randomly selected women who delivered at term. Maternal ferritin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 29 publications
2
31
0
2
Order By: Relevance
“…While CRP and ESR correlated well with each other in this study, neither measure correlated with SLE activity or pregnancy outcomes in this cohort. On the other hand, studies in healthy women suggest that an elevated serum ferritin level mid-gestation is associated with an increased risk for preterm delivery 12 13. In our study, ferritin was associated with earlier delivery, suggesting a role of inflammation in the preterm delivery in this population.…”
Section: Discussionsupporting
confidence: 47%
“…While CRP and ESR correlated well with each other in this study, neither measure correlated with SLE activity or pregnancy outcomes in this cohort. On the other hand, studies in healthy women suggest that an elevated serum ferritin level mid-gestation is associated with an increased risk for preterm delivery 12 13. In our study, ferritin was associated with earlier delivery, suggesting a role of inflammation in the preterm delivery in this population.…”
Section: Discussionsupporting
confidence: 47%
“…One of them reported that, after adjusting for various possible confounding factors, the odds ratio for extreme quartiles (>64.5 versus <26.0 ng/mL) of ferritin was 1.3 (95% CI 0.8, 2.1). Stratified analyses indicated that elevated maternal serum ferritin was associated with an increased risk of preterm premature rupture of membranes (OR = 2.1; 95% CI 1.1, 4.1), but not with spontaneous preterm labour (OR = 0.9; 95% CI 0.4, 1.7) or induced preterm delivery (OR = 1.1; 95% CI 0.6, 2.0) [25]. Considering 60% prevalence rate of anaemia during pregnancy in India, serum iron levels were also done to eliminate anaemia as the confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between serum ferritin and pregnancy outcome is confounded by several of the same factors that complicate the assessment of anaemia. Maternal infection, inflammation and hypertensive disorders are all associated with a higher incidence of preterm delivery and fetal growth restriction (70)(71)(72)(73) . Thus, whilst it appears from observational studies that serum ferritin concentrations < 30 mg/l during the second half of pregnancy are protective (62) , this is most probably because the risks associated with these confounders are much greater than those associated with depletion of maternal Fe stores.…”
Section: Assessment Of Maternal Body Iron Storesmentioning
confidence: 99%